Certificação de frutas no Brasil: influências na coordenação e gerenciamento das cadeias de suprimentos - Santos, Renata Romaguera Pereira dos (Universidade Federal de São Carlos, 2008)
The fruit certification in Brazil is a strategy adopted by the supply chain as a means of generating value and reduction of informational asymmetries between buyers and sellers. This strategy comes as a demand result from consumers for safer products and products of superior quality. It is also influenced by the possibility of paying higher prices and conquer of the increasingly competed markets as a result of globalization. The adoption of this strategy creates the need for greater interaction between the players of the chains, influencing the coordination and management of them, through the adoption of governance structures that allow reduction of transaction costs involved in such chains. The main objective of the study was to identify whether these governance structures are influenced by the agent of regulatory certifications, analyzing cases of private initiatives (GO Carrefour, EurepGap, TNC), of public and private initiative (PIF) and initiative of NGOs (Organic and Fair Trade). The study was executed through multi-case studies with producers, distributors and agents directly involved in the fruit certification process, faced with the theories of New Institutional Economics and Supply Chain Management. The conclusion to which it comes from the study is that coordination and management of the chains are not necessarily influenced by the initiative of the regulatory agent, but are a result of the market to which the certificate is intended and the institutional environment in which each certification is inserted.
Keywords: Certificação; Frutas Controle de qualidade; Cadeia de suprimentos; Governança; ENGENHARIAS::ENGENHARIA DE PRODUCAO